2022
DOI: 10.2147/ijgm.s348945
|View full text |Cite
|
Sign up to set email alerts
|

An Oxidative Stress-Related Genes Signature for Predicting Survival in Bladder Cancer: Based on TCGA Database and Bioinformatics

et al.

Abstract: Background Oxidative stress (OS) responses have been linked to oncogenesis and tumor progression and have recently been regarded as a potential strategy for tumor therapy. However, OS-related therapeutic targets have not been identified to date in the bladder cancer (BC). Methods The mRNA expression and clinical data of BC were downloaded from the public database. Prognostic risk score signature was constructed using LASSO Cox regression analysis. External validation wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…An increasing number of studies have confirmed that oxidative stress plays a crucial role in carcinogenesis and tumor treatment [ 25 27 ]. The construction of prognostic models based on public databases provides a more comprehensive clinical genetic prognostic value, and oxidative stress-based prognostic models are becoming a research hotspot for predicting the survival prognosis of different cancers [ 28 30 ]. However, the predictive value of oxidative stress-based prognostic models for the prognosis of CRC patients is still unknown and deserves further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies have confirmed that oxidative stress plays a crucial role in carcinogenesis and tumor treatment [ 25 27 ]. The construction of prognostic models based on public databases provides a more comprehensive clinical genetic prognostic value, and oxidative stress-based prognostic models are becoming a research hotspot for predicting the survival prognosis of different cancers [ 28 30 ]. However, the predictive value of oxidative stress-based prognostic models for the prognosis of CRC patients is still unknown and deserves further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress-related signatures have been established in acute myeloid leukemia ( Dong et al, 2021 ), melanoma ( Yang et al, 2021 ), clear-cell renal cell carcinoma ( Wu Y. et al, 2021a ), gastric cancer ( Wu Z. et al, 2021b ), head and neck squamous cell carcinoma ( Wang and Zhou, 2021 ), glioma ( Lu et al, 2021 ), and bladder cancer ( Zhang et al, 2022 ). Alterations in redox status accompanied by increased production of ROS have been implicated in CRC ( Lee et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…ROS experimentally induce a long interspersed expression of nuclear element-1 encoded protein expression and promote migration in bladder cancer cells [35]. The use of oxidative stress biomarkers and the oxidative stress-related gene signature to guide treatment decisions along with the development of immunotherapy may benefit the patient [36]. Furthermore, the increase in ROS may be associated with impairment in the microenvironment of cancer cells [37].…”
Section: Discussionmentioning
confidence: 99%